Kombinasi Ekstrak Daun Pandan Wangi ( Pandanus amaryllifolius Roxb.) dan Buah Mengkudu (Morinda citrifolia) sebagai Antifungi terhadap Jamur Penyebab Ketombe - AMBARWATI AMBARWATI; TANTI AZIZAH SUJONO; RETNO SINTOWATI (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Dandruff is a scalp problem which causes itching and hair loss. It causes by microorganisms, especially fungi. Pandan Wangi (Pandanus amaryllifolius Roxb.) leaves and Noni (Morinda citrifolia) fruit are known have antifungal eff ect. The aim of this study was to determine the combination of 96% ethyl acetate extract of Pandan leaves and 96% ethanol extract of Noni fruit could inhibit fungal which isolated from dandruff . The fungi were isolated from dandruff sample on PDA (Potatoes Dextro Agar) and it was purifi ed. Based on the research, it was known the density of fungi was 9.2x108 colonies/ gram. Purifi ed from 17 types of fungal isolates in dandruff sample. The inhibition test of EPW:EP (1:1) showed that 82.4% fungal isolates inhibited, the diameter of inhibition zone ranging between 15-35 mm.There are three species of fungi: Aspergillus sp, Paecylomyces varotii, Candida sp (non albicans) and 1 isolate was yeast. The active compound in Pandan leaves extract: phenol (9.42% w/w) and fl avonoids (4.39% w/w), while in Noni fruit extract: alkaloids (1.97% w/w), phenol (12.50% w/w) and fl avonoids (8.61% w/w). It can be concluded that the combination of Pandan Wangi leaves and Noni fruit extract have potential used as anti-dandruff shampoo.